2019
DOI: 10.1159/000504604
|View full text |Cite
|
Sign up to set email alerts
|

Skeletal Muscle Mass Influences Tolerability and Prognosis in Hepatocellular Carcinoma Patients Treated with Lenvatinib

Abstract: <b><i>Background:</i></b> Low skeletal muscle mass is significantly associated with severe adverse events (AEs) from chemotherapy, and low tolerability leads to decreased survival. We aimed to investigate whether body skeletal muscle mass is correlated with tolerability and prognosis in patients with hepatocellular carcinoma (HCC) treated with lenvatinib. <b><i>Methods:</i></b> This multicenter, retrospective study was conducted at five locations in Japan. We inc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
97
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 69 publications
(103 citation statements)
references
References 28 publications
4
97
2
Order By: Relevance
“…Furthermore, a cohort study of European Caucasian cirrhotic patients with advanced HCC treated with sorafenib showed that low SMI was a predictor of reduced survival and cancer treatment toxicity [ 58 ]. Recently, Uojima et al showed the number of severe adverse advents during the first two months of lenvatinib treatment was significantly associated with low SMI in 100 patients with HCC [ 59 ]. Low muscle mass has been already demonstrated to be a strong and independent risk factor for mortality in advanced HCC patients [ 60 ].…”
Section: Implications Of Muscle Wasting In Clinical Outcomes In Pamentioning
confidence: 99%
“…Furthermore, a cohort study of European Caucasian cirrhotic patients with advanced HCC treated with sorafenib showed that low SMI was a predictor of reduced survival and cancer treatment toxicity [ 58 ]. Recently, Uojima et al showed the number of severe adverse advents during the first two months of lenvatinib treatment was significantly associated with low SMI in 100 patients with HCC [ 59 ]. Low muscle mass has been already demonstrated to be a strong and independent risk factor for mortality in advanced HCC patients [ 60 ].…”
Section: Implications Of Muscle Wasting In Clinical Outcomes In Pamentioning
confidence: 99%
“…Recently, sarcopenia has been recognized as a poor prognostic factor in various fields of clinical medicine, including cancer [ 4 , 5 , 6 ]. Sarcopenia has been reported to worsen the prognosis of patients, with u-HCC patients treated with sorafenib and lenvatinib [ 7 , 8 , 9 , 10 ]. Chronic liver disease (CLD), the underlying disease of HCC, is considered a representative cause of secondary sarcopenia, as the liver is a central organ of nutrient metabolism [ 3 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…Moreover, the selection bias was correlated with the outcome. The multivariate analysis showed that an SNP combination pattern of the NOS3 rs2070744 and FGFR4 rs351855 genotypes was an independent factor of lenvatinib response, and a previous report showed that the factors significantly associated with poor OS included skeletal muscle mass index and ALBI grade 42 . Second, there was no control arm in the present study.…”
Section: Discussionmentioning
confidence: 72%